Respostas
respondido por:
32
AB --> d² = (2-(-1))² + (6-2)²
AB --> d² = (2+1)² + 4²
AB --> d² = 3² + 4²
AB --> d² = 9+16
AB --> d² = 25
d = √25
dAB = 5
dBC
d² = (5-2)² + (2-6)²
d² = 3² + (-4)²
d² = 9 + 16
d² = 25
d = 5
dAC
d² = (5-(-1))² + (2-2)²
d² = (5+1)²
d² = 6²
dAC = 6
P = AB+BC+AC
Perímetro = 5+5+6
P = 16
Determinante:
-1...2...1
2....6...1
5....2....1
D = -6+4+10-30-5+2
D = -25
A = |-25|/2
A = 25/2
A = 12,5
AB --> d² = (2+1)² + 4²
AB --> d² = 3² + 4²
AB --> d² = 9+16
AB --> d² = 25
d = √25
dAB = 5
dBC
d² = (5-2)² + (2-6)²
d² = 3² + (-4)²
d² = 9 + 16
d² = 25
d = 5
dAC
d² = (5-(-1))² + (2-2)²
d² = (5+1)²
d² = 6²
dAC = 6
P = AB+BC+AC
Perímetro = 5+5+6
P = 16
Determinante:
-1...2...1
2....6...1
5....2....1
D = -6+4+10-30-5+2
D = -25
A = |-25|/2
A = 25/2
A = 12,5
Perguntas similares
7 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás